Bottom-up and top-down control of dispersal across major organismal groups. Issue 12 (December 2018) - Fronhofer, Emanuel; Legrand, Delphine; Altermatt, Florian; Ansart, Armelle; Blanchet, Simon; Bonte, Dries; Chaine, Alexis; Dahirel, Maxime; De Laender, Frederik; De Raedt, Jonathan; di Gesu, Lucie; Jacob, Staffan; et al.
Abstract Ecology and evolution unfold in spatially structured communities, where dispersal links dynamics across scales. Because dispersal is multicausal, identifying general drivers remains challenging. In a coordinated distributed experiment spanning organisms from protozoa to vertebrates, we tested whether two fundamental determinants of local dynamics, top-down and bottom-up control, generally explain active dispersal. We show that both factors consistently increased emigration rates and use metacommunity modelling to highlight consequences on local and regional dynamics. In a coordinated distributed dispersal experiment involving seven laboratories, the authors show that both top-down predation risk and bottom-up resource limitation increase emigration rates across 21 species ranging from protozoa to vertebrates.